Urban teens in the library research and practice - Agosto, Denise E.; Hughes-Hassell, Sandra; Agosto, Denise E. (IG library, 2010)
"Urban Teens in the Library" is the perfect solution for the concerns and uncertainty many librarians face when supporting this group of patrons and students. From a team of experts who have researched the information habits and preferences of urban teens to build better and more effective school and public library programs, this book will show readers: the importance of moving beyond stereotypes and revamping library services; the value of street lit and social networking; and, how a library website can meet the information needs of teens. This groundbreaking book is relevant to all librarians working with urban teens and looking for ways to reach out to them.